PERANCANGAN STRATEGI PENGUATAN IMPLEMENTASI KEBIJAKAN REHABILITASI HUTAN DAN LAHAN STUDI KASUS DI DESA BANGUNJAYA, KECAMATAN CIGUDEG, KABUPATEN BOGOR, JAWA BARAT - Raditya Machdi Rachman; Arif Satria; Gendut Suprayitno (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2016)
This study was conducted to measure the implementation gap of forest and land rehabilitation (RHL) policy against its objectives, namely maintaining life support systems, and designing strategies to strengthen its subsequent implementation. This study took a case study on the implementation of RHL at Bangunjaya Village, Cigudeg District of Bogor. The assessment used three parameters based on Permenhut No P.39/Menhu-II/2010 including regional, institutional, and technological parameters as well as community participation. Each parameter was weighed by the ranking method based on interviews with the experts. The strategy design was conducted using the Analytic Network Process (ANP). The research results showed that the level of successful implementation in Bangunjaya RHL is 66.3%, categorized as "medium level". The lowest result is in the technological conformity parameter i.e. 11.57%. The design strategy is focused on increasing the success of the conformity of the technology and increase of community participation. The results of the weighting using ANP strategic priority, the priority strategy for the following RHL policy implementation to reach its target is the strengthening of the capacity in conducting activities and involving the community with a weight of 34.8%. The strengthening of the capacity includes streamlining the RHL paradigm RHL by not only growing but also enriching knowledge of overall forest utilization and technical optimization of land use.Keywords: strategic planning, policy implementation, forest and rehabilitation, Analytic Network Process (ANP)